Rancang Bangun Alat Peraga Gerak Berbasis Game Edukasi pada Mata Pelajaran SKI Siswa Madrasah Ibtidaiyah - Khasiriyah, Aimatul; Rofiâ€™ah, Siti (Prodi PGMI STAI Al-Akbar Surabaya, 2025)
Learning Islamic Cultural History (SKI) at the Madrasah Ibtidaiyah level still requires instructional media that can optimally enhance studentsâ€™ engagement and understanding. This study aimed to design and develop a motion-based teaching aid integrated with educational games for use in SKI learning at Madrasah Ibtidaiyah. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were 22 sixth-grade students of MI Salafiyah Syafiâ€™iyah Seblak Jombang. Data were collected through questionnaires, observations, interviews, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques to determine the feasibility and effectiveness of the developed instructional media. The results showed that the motion-based teaching aid integrated with educational games was considered highly feasible and effective for use in SKI learning at Madrasah Ibtidaiyah. This was indicated by the expert validation results with a feasibility percentage of 91%, and the studentsâ€™ responses, with an average percentage of 88.6%. Both of which fall into the â€œvery feasibleâ€ category. The use of this media increased student engagement, supported better understanding of SKI materials, and created a more interactive and enjoyable learning atmosphere. Therefore, the motion based teaching aid integrated with educational games is suitable for use as an innovative instructional medium in SKI learning at Madrasah Ibtidaiyah.